Effect of nano-yttria stabilized zirconia addition on the microstructure and mechanical properties of Ti6Al4V parts manufactured by selective laser melting. (15th October 2019) - Hattal, Amine; Chauveau, Thierry; Djemai, Madjid; Fouchet, Jean Jacques; Bacroix, Brigitte; Dirras, Guy
Abstract: This study presents the results of selective laser melting (SLM) of Ti6Al4V reinforced with 1% and 2.5% (wt%) nano yttria-stabilized zirconia (nYSZ). The bulk parts showed a very high building density which means that the melting parameters were optimal. X-ray diffraction analysis confirmed the existence of a near-alpha microstructure. No change in grains shape was noticed after the addition of nYSZ, columnar and lamellar grains remained present. The microhardness of Ti6Al4V was greatly enhanced from 340 HV to 511 HV after the addition of nYSZ which is the highest recorded value so far. The maximum values of yield stress and compressive strengths were 1302 MPa and 1751 MPa, respectively, compared to 840 MPa and 1250 MPa, respectively, for the SLMed Ti6Al4V. Graphical abstract: Unlabelled Image Highlights: Homogenous powder blend of Ti6Al4V and nYSZ was obtained. β peaks in SLMed parts were only found after addition of 1% and 2.5% of nYSZ to Ti6Al4V. Residual stress decrease shifted Ti6Al4V HT, XRD peaks toward lower angles. Microhardness increased from 340 to 511 HV with nYSZ addition to Ti6Al4V matrix. Addition of 1% of nYSZ to Ti6Al4V increased the compression strength without ductility loss.